Anaphora resolution and word-order across adulthood: Ageing effects on online listening comprehension. Issue 1 (20th July 2020) - Fotiadou, Georgia; Muñoz, Ana I. Pérez; Tsimpli, Ianthi Maria
Abstract : In this visual-world paradigm we investigated the processing and interpretation of two overt subject anaphoric expressions in Greek, a null-subject language with a relatively free word-order, in relation to specific linguistic properties and whether these differ across adulthood. Specifically, we explored whether changes in anaphoric type ( o ídhios vs. aftós ) and syntactic complexity (SVO vs. OVS word-orders) had similar effects in how reference was processed and finally resolved by young and elderly adults. We analysed (a) fixation duration in subject and object antecedent pictures to examine online processing and (b) offline responses in comprehension questions to investigate final interpretation, i.e., ambiguity resolution. Our offline results revealed that pronominal resolution patterned across age groups: A clear subject preference of o ídhios ('the same') was drawn from results irrespective of the word-order used, suggesting that this expression is preferentially linked to an element in prior discourse that has a parallel subject grammatical role, due to its focus feature (though OVS boosted the less preferred object readings). Aftós ('he'), a pronoun previously suggested sensitive to topic-shift, was overall proved ambiguous for both young and elderly adults. An age effect was qualified by significant differences in online processing of both subject expressions, as evidenced by fixation on both antecedent pictures. Interestingly, syntactic complexity (OVS structures) interacted with age in the case of o ídhios, raising fixation in subject antecedents among young, compared to the elderly adults. Age, but not linguistic manipulation, modulated processing of the anaphoric pronoun aftós and of object antecedent pictures overall.